2015
DOI: 10.1177/1074248415612593
|View full text |Cite
|
Sign up to set email alerts
|

Prospects for Creation of Cardioprotective Drugs Based on Cannabinoid Receptor Agonists

Abstract: Cannabinoids can mimic the infarct-reducing effect of early ischemic preconditioning, delayed ischemic preconditioning, and ischemic postconditioning against myocardial ischemia/reperfusion. They do this primarily through both CB1 and CB2 receptors. Cannabinoids are also involved in remote preconditioning of the heart. The cannabinoid receptor ligands also exhibit an antiapoptotic effect during ischemia/reperfusion of the heart. The acute cardioprotective effect of cannabinoids is mediated by activation of pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 68 publications
(180 reference statements)
2
22
0
3
Order By: Relevance
“…Both CB1R and CB2R were expressed in adult rat cardiomyocytes [50]. In the myocardial I/R model, we found that propofol conditioning-induced antioxidation and cardioprotection could be fully reversed by CB2R antagonist AM630 (Figures 6 and 7).…”
Section: Discussionmentioning
confidence: 91%
“…Both CB1R and CB2R were expressed in adult rat cardiomyocytes [50]. In the myocardial I/R model, we found that propofol conditioning-induced antioxidation and cardioprotection could be fully reversed by CB2R antagonist AM630 (Figures 6 and 7).…”
Section: Discussionmentioning
confidence: 91%
“…Ouabain, and potentially other CTS, could therefore be added to the list of paracrine/autocrine factors that are released during preconditioning ischemia and trigger protection by binding to their respective receptors. Some of the most promising cardioprotective candidate drugs to date, opioid and cannabinoid receptor agonists [68,69] or adenosine receptor agonists [70], belong to this category.…”
Section: Prospect and Future Directionsmentioning
confidence: 99%
“…Initial studies on the role of cannabinoids in cardiac ischemia were predominantly performed ex vivo in papillary muscles or isolated heart. In these models, endocannabinoids ameliorated ischemia/reperfusion injury and reduced the early phase of heart remodeling (reviewed in [13,60,61]). It also has been pointed at the role of CB2 receptor activation in remote ischemic preconditioning [62][63][64][65].…”
Section: Ischemia-reperfusion Injurymentioning
confidence: 99%
“…The CB2 receptors, on the contrary, may play a compensatory anti-inflammatory, anti-oxidative, and anti-atherogenic role [9,10] contributing to cardiovascular protection.Nevertheless, the role of cannabinoid receptors in the heart under several pathological conditions remains controversial. Recent studies on hemodynamic, antiarrhythmic, and cardiometabolic effects of cannabinoids have been highlighted in several excellent reviews [2,3,[11][12][13][14]. Hence, these topics are not in the scope of this chapter.The aim of this review was to up-date on recent findings and controversies on the role of ECS in the myocardial injury with emphasis on pathophysiological processes such as left ventricular remodeling, cardiac fibrosis, hypertrophy, and endothelial dysfunction.…”
mentioning
confidence: 99%
See 1 more Smart Citation